Social care causes of delayed transfer of care (DTOC) from hospital for older people: Unpicking the nuances of 'provider capacity' and 'patient choice'. (16th July 2022) - Gridley, Kate; Baxter, Kate; Birks, Yvonne; Newbould, Louise; Allan, Stephen; Roland, Daniel; Malisauskaite, Gintare; Jones, Karen
Abstract: Unnecessarily prolonged stays in hospitals can have negative impacts on patients and present avoidable costs to health and social care systems. This paper presents the qualitative findings of a multi‐methods study of the social care causes of delayed transfers of care (DTOC) for older people in England. The quantitative strand of this study found that DTOC are significantly affected by homecare supply. In this paper, we explore in depth how and why social care capacity factors lead to delays, from the perspectives of those working within the system. We examined the local transfer arrangements in six English local authority (LA) sites that were purposively sampled to include a range of DTOC performance and LA characteristics. Between March and December 2018, 52 professionals involved in arranging or facilitating discharge from hospitals in these sites provided qualitative data, primarily through semi‐structured interviews. Topics included discharge teams and processes, strategic issues and perceived causes of delays. The thematic analysis uncovered the nuances behind the causes of DTOC previously categorised broadly as 'provider capacity' and 'patient choice'. In particular, our analysis highlights the lack of fit between available provision and the needs of people leaving hospital (theme 1); workforce inconsistencies (theme 2) and a myth of patient choice (theme 3). We are now at a turning point in the development of policy to reduce DTOC in the English system, with the full implications of a new national discharge to assess programme yet to be seen. Our research shows the significance of the alignment of service capacity, including the type and location of provision, with the needs and preferences of those leaving hospital. As the new system becomes established, attendance to such nuances behind blockages in the system will be more important than ever.